The resource requirements of perioperative patient warming in German hospitals – the results of a prospective, multicenter activity-based costing study - Stefan Nardi-Hiebl; Jan Wallenborn; Martin Schniertshauer; Tilo Koch; Tobias Gruebl; Alexander Torossian (BMC Anesthesiology)
Abstract Background Perioperative warming is essential in preventing hypothermia during surgery, a condition linked to adverse outcomes like increased infection rates, impaired coagulation, and extended hospital stays. Despite the availability of various active warming methods, such as forced-air warming (FAW) and electric warming systems, their implementation and associated costs vary significantly across hospitals, impacting resource allocation and patient care. Method This study used a prospective, multicenter, activity-based costing approach across four German hospitals with diverse capacities. The activity-based costing model identified and measured staff time, material use, and direct costs linked to perioperative warming processes in a sample of 225 surgical patients. Warming processes were assessed across stages, including pre-warming, intraoperative warming, and post-anesthesia care. Results Findings show significant variability in the time and cost associated with perioperative warming across institutions. The average total cost per patient between all sites ranged from EUR 3.52 to EUR 49.26, with an overall mean cost of EUR 12.29 per patient. Staff time also varied, with nurses contributing most of the required time dedicated to warming activities. At all sites, FAW was the available method during surgery, but inconsistent practices and reliance on supplemental strategies lead to considerable cost variations. Conclusion This study illustrates potential operational and financial challenges of perioperative warming, revealing significant variability in costs and resource requirements across hospitals, influenced by institutional infrastructure, workflow efficiency and case mix. The findings also emphasize the importance of optimizing workflows and adopting best practices tailored to resource constraints. Future research should address these gaps by exploring cost-effective warming protocols, balancing efficiency with care quality, and refining workflows to enhance patient outcomes.